Climbing adaptations, locomotory disparity and ecological convergence in ancient stem 'kangaroos'. Issue 2 (6th February 2019) - Den Boer, Wendy; Campione, Nicolás E.; Kear, Benjamin P.
Abstract : Living kangaroos, wallabies and rat-kangaroos (Macropodoidea) constitute the most ecologically diverse radiation of Australasian marsupials. Indeed, even their hallmark bipedal hopping gait has been variously modified for bounding, walking and climbing. However, the origins of this locomotory adaptability are uncertain because skeletons of the most ancient macropodoids are exceptionally rare. Some of the stratigraphically oldest fossils have been attributed to Balbaridae—a clade of potentially quadrupedal stem macropodoids that became extinct during the late Miocene. Here we undertake the first assessment of balbarid locomotion using two-dimensional geometric morphometrics and a correlative multivariate analysis of linear measurements. We selected the astragalus and pedal digit IV ungual as proxies for primary gait because these elements are preserved in the only articulated balbarid skeleton, as well as some unusual early Miocene balbarid-like remains that resemble the bones of modern tree-kangaroos. Our results show that these fossils manifest character states indicative of contrasting locomotory capabilities. Furthermore, predictive modelling reveals similarities with extant macropodoids that employ either bipedal saltation and/or climbing. We interpret this as evidence for archetypal gait versatility, which probably integrated higher-speed hopping with slower-speed quadrupedal progression and varying degrees of scansoriality as independent specializations for life in forest and woodland settings.